INTELLECTUAL CAPITAL DISCLOSURE: KAITANNYA DENGAN UKURAN PERUSAHAAN, PERTUMBUHAN LABA DAN NILAI PERUSAHAAN - Bonar Pangaribuan; Hisar Pangaribuan (Fakultas Ekonomi Universitas Advent Indonesia, 2020)
Bank is the business industry that runs with various, even complex sources of capital, therefore it is necessary to have adequate management and disclosure of intellectual capital in this industry. The aims of this study is to determine the effect of company size and profit growth on intellectual capital and to find out the effect of intellectual capital on firm value banking companies in Southeast Asia. By using descriptive and verification research methods, it is expected that this research can explain the state of banking companies in Southeast Asia and verify research and explain the gaps that exist in previous studies related to this research hypothesis. This study uses secondary data and the sample is taken using a purposive sampling method. The data obtained and met the research criteria were processed using STATA. These findings indicate that company size, as seen from total assets, has a significant and positive effect on disclosure of intellectual capital, earnings growth has a significant and negative effect on disclosure of intellectual capital, and disclosure of intellectual capital has no significant effect on firm value.